Pembuatan Bahan Bakar Padat Dari Pelepah Sawit Menggunakan Proses Torefaksi Pada Variasi Suhu Waktu Torefaksi - Rina Maryenti; Komalasari Komalasari; Zuchra Helwani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Oil Palm Fronds can be used as alternative energy source by using torrefaction process. Oil Palm Fronds has a calorific value of 15439.39 kJ/kg. The calorific value can be increased by torrefaction. Torrefaction is a pre-treatment process of biomass into solid fuel within temperature range of 200 - 300 oC in an inert condition. This research aims to produce solid fuel from oil palm fronds and study the effect of variation in temperature and time torrefaction towards characteristic of solid fuel resulted. Torrefaction of oil palm fronds was using fixed bed horizontal reactor at temperature of 250 - 300 oC and time of 20 - 40 minutes. Product quality resulted was calorific value, mass yield, energy yield and proximate. The result obtained for calorific value in range was 18152.26 - 24060.32 kJ/kg, mass yield was 45.22 - 75.04 %, and energy yield was 70.49 - 88.23 %. Proximate analysis resulted in the form of moisture content was 3.42 - 5.44 %, ash content was 4.67 - 6.89 %, volatile content was 38.63 - 65.34 %, and fixed carbon was 24.55 - 51.06 %.Keywords: calorific value, energy yield, mass yield, oil palm fronds,torrefaction.